Bilateral Silicone Granulomas Mimicking Breast Cancer Recurrence on 18F-FDG PET/CT. (February 2021) - Fernandes Vieira, Victor; Dubruc, Estelle; Raffoul, Wassim; Prior, John O.; Meyer, Marie
Abstract : Abstract: We report the case of a 45-year-old woman with a history of right breast reconstruction with silicone implant for breast cancer. An 18 F-FDG PET/CT performed several years later revealed the presence of 18 F-FDG–avid nodules at the periphery of the silicone implant, in the right internal mammary chain, and in the contralateral breast. Needle core biopsies were positive for bilateral silicone granulomas, without any sign of malignancy. This case displays intense 18 F-FDG uptake in silicone granulomas affecting the contralateral breast after implant reconstruction.